Tuning the Color Palette of Fluorescent Copper Sensors through Systematic Heteroatom Substitution at Rhodol Cores - Jia, Shang (ACS Chem Biol, 2017)
Copper is an essential nutrient for sustaining life, and emerging data have expanded the roles of this metal in biology from its canonical functions as a static enzyme cofactor to dynamic functions as a transition metal signal. At the same time, loosely bound, labile copper pools can trigger oxidative stress and damaging events that are detrimental if misregulated. The signal/stress dichotomy of copper motivates the development of new chemical tools to study its spatial and temporal distributions in native biological contexts such as living cells. Here, we report a family of fluorescent copper sensors built upon carbon-, silicon-, and phosphorus-substituted rhodol dyes that enable systematic tuning of excitation/emission colors from orange to near-infrared. These probes can detect changes in labile copper levels in living cells upon copper supplementation and/or depletion. We demonstrate the ability of the carbon-rhodol based congener, Copper Carbo Fluor 1 (CCF1), to identify elevations in labile copper pools in the Atp7a(−/−) fibroblast cell model of the genetic copper disorder Menkes disease. Moreover, we showcase the utility of the red-emitting phosphorus-rhodol based dye Copper Phosphorus Fluor 1 (CPF1) in dual-color, dual-analyte imaging experiments with the green-emitting calcium indicator Calcium Green-1 to enable simultaneous detection of fluctuations in copper and calcium pools in living cells. The results provide a starting point for advancing tools to study the contributions of copper to health and disease and for exploiting the rapidly growing palette of heteroatom-substituted xanthene dyes to rationally tune the optical properties of fluorescent indicators for other biologically important analytes.